Reformasi Birokrasi dalam Peningkatan Pelayanan Publik pada Dinas Perindustrian, Perdagangan, Koperasi dan Usaha Kecil Menengah Kabupaten Paser Kalimantan Timur - Siti Nabawiyah; Nuraisyah; Ani Susanti (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study discusses bureaucratic reform in improving public services at the Department of Industry, Trade, Cooperatives, and Small and Medium Enterprises (DISPERINDAGKOP UKM) of Paser Regency, East Kalimantan. This research uses a qualitative approach with a case study method, aiming to understand the role of bureaucratic reform in creating more effective, efficient, and transparent public services. A sample of 15 people was taken for this study. The research findings indicate that bureaucratic reform at DISPERINDAGKOP UKM contributes to improving service quality, strengthening human resource capacity, utilizing technology, and increasing community participation. However, there are several obstacles, such as limited human resources, regulations, and adequate infrastructure. Strategic steps, such as developing a reform roadmap, strengthening institutional structures, and implementing a meritocracy system, have been undertaken to address these challenges. This study emphasizes the importance of bureaucratic reform in supporting SME growth, enhancing competitiveness, and improving public trust in local governments.